2007
DOI: 10.1098/rstb.2007.2176
|View full text |Cite
|
Sign up to set email alerts
|

Water pollution by agriculture

Abstract: Agriculture disrupts all freshwater systems hugely from their pristine states. The former reductionist concept of pollution was of examining individual effects of particular substances on individual taxa or sub-communities in freshwater systems, an essentially ecotoxicological concept. It is now less useful than a more holistic approach that treats the impacts on the system as a whole and includes physical impacts such as drainage and physical modification of river channels and modification of the catchment as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(191 citation statements)
references
References 65 publications
3
179
0
9
Order By: Relevance
“…However, WQI min was not able to separate the reference station and the others to a large extent, though some significant differences for the entire months were observed. One explanation of this can be that since both urban and domestic waste are also sources of the parameters included in the calculation of WOI min in rivers, streams and lakes (Carpenter et al, 1998;Mander et al, 2000;Neal and Jarvie, 2005;Jarvie et al, 2008 andMoss, 2008) it may not have clearly separated the affected sampling stations in the present study.…”
Section: Resultsmentioning
confidence: 75%
“…However, WQI min was not able to separate the reference station and the others to a large extent, though some significant differences for the entire months were observed. One explanation of this can be that since both urban and domestic waste are also sources of the parameters included in the calculation of WOI min in rivers, streams and lakes (Carpenter et al, 1998;Mander et al, 2000;Neal and Jarvie, 2005;Jarvie et al, 2008 andMoss, 2008) it may not have clearly separated the affected sampling stations in the present study.…”
Section: Resultsmentioning
confidence: 75%
“…Such effects are called negative externalities because they are usually non-market effects and therefore their costs are not part of market prices. Negative externalities are one of the classic causes of market failure whereby the polluter does not pay the full costs of their actions, and therefore these costs are called external costs (Baumol & Oates 1988;Pretty et al 2000Pretty et al , 2003aDobbs & Pretty 2004;Moss 2008).…”
Section: Side Effects and Externalitiesmentioning
confidence: 99%
“…For example, Bowes et al [95] found that shading had far more impact on algal growth in the River Thames in England than reducing in-stream P concentrations. These uncertainties have led to more holistic approaches to eutrophication control in the hope that combined actions will have more chance of success [31]. ), which are typically close to limiting concentrations for algal growth in UK lowland rivers [95].…”
Section: Waterbody Characteristicsmentioning
confidence: 99%
“…Agriculture is now considered to be a major underlying and persistent cause of eutrophication in many catchments around the world [30][31][32][33]. However, nutrient loadings from agriculture are not easy to mitigate due to their storm-dependent and diffuse nature, and improvements in the chemical and/or ecological quality of many waterbodies impacted by farming still need to be achieved.…”
Section: Introductionmentioning
confidence: 99%